MOTIF DRIVER PEREMPUAN OJEK ONLINE DI KOTA SURABAYA DALAM PERSPEKTIF BUDAYA JAWA: Motif, Ojek Perempuan, Budaya Jawa - Rainrizky, Vhiordy Mitha; Huda, Anam Miftakhul (Universitas Negeri Surabaya, 2023)
The motives of female online motorcycle taxi drivers in the city of Surabaya are quite diverse, where each individual has their own motivation to choose to work as an online motorcycle taxi driver. However, the actions that women choose to become online ojek drivers are different from the stigma in Javanese culture, Javanese culture places women as kanca wingking more than men and women are seen as only able to macak, manak, cook. This study aims to determine the motives of female online motorcycle taxi drivers in the city of Surabaya from a Javanese cultural perspective. This research is a qualitative research using phenomenological methods. The data collection technique in this study was carried out by means of in-depth interviews targeted at five female online motorcycle taxi drivers. Data analysis in this study was done by reducing data, presenting data, and drawing conclusions. The findings from this study are that the informants have different motives, namely the mindset to always be productive and economic factors. This is certainly not in harmony with the stigma of Javanese culture that has developed in society regarding the view that women who become online motorbike taxi drivers are a taboo.